Socialization of Cyber Crime Threats Ahead of the 2024 Election for the Online Ojek Community: Sosialisasi Ancaman Kejahatan Siber Menjelang Pemilu 2024 untuk Komunitas Ojek Online - Syahtriatna Djusar; Muhamad Sadar (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Ahead of the 2024 General Election, cyber threats are expected to increase along with the increasingly massive use of cyberspace for political purposes. Members of the Online Ojek Community are a group of people who are vulnerable to being targeted and "perpetrators" of cybercrimes. This is because the online driver community always interacts with digital devices and the general public. The dedication team has carried out the activity stages, starting with a questionnaire of 16 questions, lectures, and outreach to 15 participants, as well as discussions and questions and answers. Related material on how to filter and test the correctness of data and information; how to act and behave in the use of social media and digital devices; how to know the rule of law in the use of digital technology. After the implementation of the activity, there was an improvement in the participants' understanding. Initially, the average participant had an adequate understanding of the number 72, after the implementation of the activity, the average participant's understanding was very good with a score of 92.86. This increased knowledge will reduce the risk of Cyber Security Threats for online motorcycle taxi drivers.